Chiral catalysts immobilized on achiral polymers: effect of the polymer support on the performance of the catalyst. (26th March 2018) - Altava, Belén; Burguete, M. Isabel; García-Verdugo, Eduardo; Luis, Santiago V.
Abstract : Achiral polymeric supports can have important positive effects on the activity, stability and selectivity of supported chiral catalysts. Abstract : Positive effects of the polymeric support on the performance of supported chiral catalysts, in terms of activity, stability and selectivity–enantioselectivity, have been reported when the support is properly selected and optimized opening the way to the design of more efficient catalytic systems.